Effects of political patronage upon police practices and police reforms during democratisation in Thailand in the period of 1992–2006 - Wong, Kai Shing (Policing and society, 2023)
In many new democracies, the police continue to be a political tool of the ruling elites, and governments are reluctant to reform the police to be a democratic police force. This article examines why these problems occur by analyzing how the police relate to ruling elites and how this relationship affects police practices and police reforms based on a case study on Thailand. By adopting the institutionalist approach concerning the impacts of informal institutions on formal institutions, this study finds that political patronage between politicians and police officers made the police a political tool of politicians in power and led to the failure to reform the police to develop democratic policing during democratisation in Thailand in the period of 1992–2006. After the 1992 uprising, businessman-politicians replaced military leaders to be patrons of police officers by manipulating police reshuffles in Thailand. Through these relationships, police officers abused their powers to aid politicians and political parties to suppress political opponents and dissent through selective law enforcement and criminal investigations. Political patronage affected police reforms through ‘constraining’ policies that were designed to increase the accountability of the police and prevent abuse of police powers, while, at the same time, ‘reinforcing’ the restructuring of police organisation and administration to strengthen the relationship of political patronage.